2018
DOI: 10.1620/tjem.245.37
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Harassment Experiences and Burnout among Academic Faculty in Japan

Abstract: The purpose of this study is three-fold: (1) to compare harassment (sexual, gender, and academic harassment both directly and indirectly experienced - i.e. "directly harassed" and "have seen or heard of someone who experienced harassment", respectively) experienced by males and females, (2) to investigate whether such experiences correlate with burnout, and (3) to explore whether social support might mitigate any such relationship between harassment and burnout. This cross-sectional study was conducted at a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…Therefore, those who scored higher for this factor may perceived gender inequality or harassment. This coincides with previous studies [14][15][16]. A previous study in Iran [28] that investigated female health workers demonstrated that trust and social participation in the workplace are beneficial to nurses, patients, and the organization, through improved communication, teamwork, and access to greater information, support, and resources.…”
Section: Interpretation Of the Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, those who scored higher for this factor may perceived gender inequality or harassment. This coincides with previous studies [14][15][16]. A previous study in Iran [28] that investigated female health workers demonstrated that trust and social participation in the workplace are beneficial to nurses, patients, and the organization, through improved communication, teamwork, and access to greater information, support, and resources.…”
Section: Interpretation Of the Findingssupporting
confidence: 90%
“…A study in Canada [15] previously highlighted the importance of the organizational climate for gender equity and demonstrated that the gender gap in academic medicine may have negative consequences for organizational effectiveness and workplace culture. We also found that utilizing women and absence of inequality or harassment at workplace alleviated women's burnout [16]. These findings suggest that organizational fairness that improves gender equity may be a useful tool to enable women to continue working.…”
Section: Introductionmentioning
confidence: 56%
“…In addition, women who belong to a sexual minority group are at risk of experiencing harassment based on their sexual orientation [47]. Workplace sexual harassment and bullying have been linked to mental health issues, such as depression and anxiety, and may contribute to the development of burnout among victims of both direct and indirect harassment [48,49,50]. Women physicians who have been victims of sexual harassment note that the experiences negatively aff ected their self-confi dence and career advancement.…”
Section: Sexual Harassmentmentioning
confidence: 99%
“…Those who experience sexual harassment in post-secondary settings suffer mental, psychological, physical, academic, and work-related consequences-including lower GPA for students and, in the case of faculty, potentially leaving academe altogether [8][9][10][11]. The negative effects of sexual harassment, moreover, can affect an entire scholarly community; recent work has shown that an environment where sexual harassment is pervasive can lead to faculty burnout among women, even if they do not experience sexual harassment directly [12].…”
Section: Introductionmentioning
confidence: 99%